Exploring How Families Do Science Together: Adult‐Child Interactions at Community Science Events. (25th May 2017) - Tuttle, Nicole; Mentzer, Gale A.; Strickler, Lacey; Bloomquist, Debra; Hapgood, Susanna; Molitor, Scott; Kaderavek, Joan; Czerniak, Charlene M.
Abstract : Promoting family learning around science represents an important opportunity to reinforce science learning during out‐of‐school time. Evidence suggests that parent‐child discourse around science can promote inferential thinking by children and help solidify their understanding of science concepts. While teacher professional development that promotes the type of discourse that encourages student inquiry is trending, interventions that assist parents in developing the same types of learning talk skills are scarce. In this descriptive study, family discourse was observed at a series of events at community centers that promote science learning, such as the zoo and the library. These events were part of a large‐scale professional development program designed to transform teaching and learning around PK–3 science. Families were scored on their interaction, discourse, and use of "talk moves" using the Discourse, Interaction, and Inquiry in Family Science rubric. The results demonstrate that the events promoted family discourse and interaction in a manner dependent on the activity context. Implications for teachers and design of family science learning activities are discussed.